Avaliação morfométrica dos hepatócitos de ratos diabéticos tratados com neem (azadirachta indica a. juss) e estreptozootocina 6 ch - Silva, Matheus Henrique Magalhães [UNESP]; Pacheco, Maria Rita [UNESP]; Girardi, Annita Morais [UNESP]; Baraldi-Artoni, Silvana Martinez [UNESP]; Dos Santos, Edanir [UNESP]; Barreiro, Fabiana Ribeiro [UNESP] (My University, 2011)
The effects of extracts from Azadirachta indica A. Juss and streptozotocin, in extreme high dilutions in dinamized systems, on hepatocyte morphometry of rats with diabetes mellitus induced by streptozotocin were evaluated. Some parameters presented significant differences among the experimental groups, but the effect of treatments to make better or worse the consequences of diabetes mellitus on liver was not detected using only the hepatocyte morphometry. The morphometric analysis evidenced that the white control group presented the highest mean values for nucleus and cytoplasm parameters, with the exception of the nuclear shape factor. However, this situation did not imply the diabetes mellitus was the cause of drastic reduction in these values, since the literature describes lower measurements for rats from the control group (non-diabetic rats).
Morphometric evaluation of hepatocytes from diabetic rats treated with neem (Azadirachta indica A. Juss) and streptozotocin 6 CH
Keywords: Diabetes mellitus; Homeopathy; Liver; Morphometry; Phytotherapy; Azadirachta indica; Rattus